Temporising external fixation of calcaneus fractures prior to definitive plate fixation: a case series. (September 2015) - Farrell, Brian M.; Lin, Carol A.; Moon, Charles N.
Abstract: Introduction: Surgical management of calcaneus fractures is technically demanding and has a high risk of wound complications. These fractures are traditionally managed with splinting until swelling has subsided, which can take weeks and leaves the fracture fragments displaced. We describe a novel protocol for the management of displaced intraarticular calcaneus fractures that utilises a temporising external fixator and staged conversion to plate fixation through a sinus tarsi approach. The goal of this technique was to enable earlier treatment with open reduction and internal fixation, minimise the amount of manipulation required at the time of definitive fixation and reduce the wound complication rate seen with the traditional extensile approach. Methods: The records of patients with displaced calcaneus fractures from 2010–2014 were reviewed retrospectively. A total of nine patients with 10 calcaneus fractures were treated using this protocol. All patients underwent ankle-spanning medial external fixation within 48 hours after injury. Patients underwent conversion to open plate fixation through a sinus tarsi approach when skin turgor had returned to normal. Time to surgery, infection rate, wound complications, radiographic alignment, and time to radiographic union were recorded. Results: The average Bohler's angle improved from 13.2 (range −2 to 34) degrees preoperatively to 34.3 (range 26 to 42) degrees postoperatively. The average time from external fixation to conversion to internal fixation was 4.8 (range 3 to 7) days. There were no immediate post-surgical complications. The average time to weight-bearing was 8.5 weeks. The average time to radiographic union was 9.5 (range 8 to 12) weeks. There were no infections or wound complications at the time of last follow-up. Conclusion: Early temporising external fixation for the acute management of displaced calcaneus fractures is a safe and effective method to reduce and stabilise the foot and may decrease the time to definitive fixation. There were no complications related to the use of the external fixator in this series.